(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2021)
The Straits of Malacca is a narrow strait located between three countries, namely Malaysia, Singapore and Indonesia. The Straits functions as the most important passage for hundreds of ships to deal with international affairs, particularly for trading purposes. Such a situation indirectly contributes to high traffic congestion and increases the risk of collision between ships, which consequently causes oil spills and damages the aquatic biosystems. Part III and Part XII of the Law of the Sea Convention 1982 (UNCLOS) would be applicable in addressing such issues, particularly Article 233. Article 233 would be the main discussion applied to analyse the extent of enforcement measures that could be taken towards ships that cause damage. Therefore, this article identifies the concept and definition of Article 233 and its application in curbing the issue of sea pollution in the Straits of Malacca. It aims to identify the measures that could be taken by the littoral states and the application of other provisions under UNCLOS 1982 in enforcing the laws in the Straits. This article also proposes suggestions and recommendations to improve on the issue of sea pollution and the obligations of the littoral states in curbing the problem. Keywords: Article 233, The Straits of Malacca, sea pollution, Straits States, ships